The impact of rural settlement expansion on educational accessibility: a patch-scale study based on 2867 Chinese counties from 2000 to 2020 - Yuan Gao; Li Tian; Zhibin Li; Yiheng Wang; An Huang; Qingsong He (Humanities & Social Sciences Communications)
Abstract Rural educational accessibility is crucial for achieving equitable education, reducing urban-rural disparities, and fostering inclusive and sustainable human settlements, which are key sustainable development goals (SDGs). Besides increasing educational facilities, the migration of rural settlements also influences educational accessibility. This study adopts a patch-scale perspective to measure the expansion patterns of rural settlements in 2867 counties across mainland China from 2000 to 2020. Utilizing the Multiscale Geographically Weighted Regression (MGWR) method, the study assesses the spatially heterogeneous impact of rural settlement expansion on educational accessibility. The findings reveal that over the past two decades, there has been a significant expansion in the area of rural settlements, predominantly characterized by outlying expansion. The total area of rural settlements at the county level has a positive effect on shortening the average distance from settlements to schools, indicating that the construction of rural settlements has facilitated educational accessibility in rural areas. However, the outlying-style development pattern has a spatially differentiated impact on accessibility, with a significant inhibitory effect observed in some northeastern and northwestern counties. These insights provide support for the construction of rural settlements. The study aims to offer policy implications for educational equity and sustainable urban-rural development in developing countries.